2021
DOI: 10.1002/cre2.482
|View full text |Cite
|
Sign up to set email alerts
|

Gingival phenotype distribution in young Caucasian women and men – An investigative study

Abstract: Objectives: To evaluate the relationship between gingival phenotype and tooth location based on selected index teeth ("Ramfjord") and assess possible differences between women and men.Material and Methods: Thirty-six women and 20 men voluntarily participated in this investigation with an average age of 23 years (min: 19; max: 37). Gingival phenotypes (GP) were assessed by transparency of a periodontal probe through the buccal gingival margin.Results: A comparable and similar GP on all index teeth was only foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 29 publications
(37 reference statements)
1
24
0
Order By: Relevance
“…Such discrepancies in the values found for KTW at thick phenotype sites may be related to different tooth regions included in the analysis of the studies assessed in the systematic review. The present study observed a positive but weak correlation between KTW and GT, which is in agreement with previous studies 13,11,40,41 . Recently, Barootchi et al 42 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Such discrepancies in the values found for KTW at thick phenotype sites may be related to different tooth regions included in the analysis of the studies assessed in the systematic review. The present study observed a positive but weak correlation between KTW and GT, which is in agreement with previous studies 13,11,40,41 . Recently, Barootchi et al 42 .…”
Section: Discussionsupporting
confidence: 94%
“…The present study observed a positive but weak correlation between KTW and GT, which is in agreement with previous studies. 13,11,40,41 Recently, Barootchi et al 42 suggested that although KTW and GT may influence the position of the gingival margin in a similar way, they would be independent of each other. Similarly, Yilmaz et al 43 observed that the modification of the gingival phenotype resulted in tissue stability and creeping attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an association between male sex and gingival thickness has been observed in Korean (Kim et al, 2021) and Indian populations, finding that the gingiva was found to be thinner and with less width in females than males (Anand et al, 2022; Kolte et al, 2014, 2019). Nevertheless, the absence of statistically significant differences between the sexes has also been reported for the same population (Shah et al, 2015) and for the Dominican (Collins et al, 2021), Portuguese (Peixoto et al, 2015), Swiss (Fischer et al, 2022), and Yemeni (Alhajj, 2020) populations. This could be explained, in part, by melatonin and hemoglobin concentrations, which differ according to ethnicity and sex (Shi et al, 2022).…”
Section: Discussionmentioning
confidence: 76%
“…Portuguese (Peixoto et al, 2015), Swiss (Fischer et al, 2022), and Yemeni (Alhajj, 2020) populations. This could be explained, in part, by melatonin and hemoglobin concentrations, which differ according to ethnicity and sex (Shi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…1, a further selection, based on reading the abstracts, resulted in the exclusion of 32. Finally, of the 14 articles eligible for full reading, only 13 were included [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The article by Das et al (2022) was not retained due to the lack of precision of the gingival thickness endpoint [ 29 ].…”
Section: Resultsmentioning
confidence: 99%